AB0150 Association of the Polymorphism of the IGH Enhancer HS1.2A with Axial-Spondyloarthritis. (9th June 2015) - Simone, D.; Canestri, S.; Ramonda, R.; Nowik, M.; Lorenzin, M.; Frallonardo, P.; Gremese, E.; Tolusso, B.; Ferraccioli, G.
Abstract : Background: Several genes besides HLA-B27 have shown to confer a predisposition to develop of the disease and different clinical manifestations within the spectrum of spondyloarthritides (SpA). A specific polymorphism of the enhancer HS1.2A of the Ig Heavy 3' regulatory region was previously described as associated to autoimmune conditions such as rheumatoid arthritis, 1 systemic sclerosis 2 and systemic lupus erythematosus 3, while no genes related to the regulation of the autoimmune response have been yet identified to be associated with SpA. Objectives: To evaluate the frequency of polymorphisms in the enhancer HS1.2A of the Ig Heavy 3' regulatory region in patients with axial-SpA from two different italian cohorts, and to identify a correlation of this genetic factor with a specific phenotype or with a different clinical presentation of the disease. Methods: We evaluated 153 patients from the Rheumatology Division of the Catholic University in Rome (Cohort 1) and 75 patients from the University of Padua (Cohort 2), for a total of 228 patients, all with a diagnosis of axial SpA according to the ASAS criteria. The patients were differentiated, according to their clinical phenotype, in ankylosing spondylitis, psoriatic spondyloarthritis, IBD-associated spondyloarthritis or undifferentiated spondyloarthritis. BASDAI, CRP and ASDAS-CRP were used to asses the inflammatory burden and the disease activity at the clinical presentation. Selective polymerase chain reaction of the region containing polymorphic HS1.2A alleles was performed 4 on all patients after informed consent and on 573 healthy subjects, matched for age, sex, and from the same geographical area, that were enrolled as control group. Results: The frequency of allele *2 of the HS1.2A enhancer in SpA patients from both the Cohort 1 and the Cohort 2 was significantly increased compared to healthy controls [Cohort 1: 64.7% vs 40.8%, p<0.001; OR 2.32 (1.85-2.90); Cohort 2: 58% p<0.001; OR 1.85 (1.36-2.5)] and also the percentage of homozygotes for that allele (genotype 2/2) [Cohort 1: 40.9% vs 15.7%, p<0.001; OR 2.67 (2.00-3.56); Cohort 2: 30.7%; p<0.001; OR 1.10 (1.30-3.00)]. No association was found with the polymorphism and the different SpA subtypes or the clinical manifestations of the disease. The patients that carried allele 2 of HS1.2A (both in homozygosis or heterozygosis) were comparable considering age of onset, inflammation or disease activity to subjects not-carriers of the allele. Conclusions: Our data show an association of SpA with the allele 2 of the gene enhancer HS1.2A, similarly for what already observed in other autoimmune diseases. The presence of this specific polymorphism of gene HS1.2A might be a marker of autoimmunity or a sign of possible B cell involvement in SpA. References: Tolusso B et al., Ann Rheum Dis 2009 Frezza D et al., Ann Rheum Dis 2007 Frezza D et al., Ann Rheum Dis 2012 Giambra V et al., Gene 2005. Disclosure of Interest: None declared